Assessing the Landscape of the Sport Industry in China: A Brief Commentary - Oscar Rhodes (Universidad Pablo de Olavide, 2024)
Sport has played a critical role in China's development since 1949, with achievements in elite sports, the hosting of Olympic games, and establishing professional leagues. The aim of China is to establish itself as a global sporting leader, influenced by the success of the US market and the rising obesity epidemic. In 2008, Chinese athletes showcased their talents at the Beijing Olympics, although concerns were raised about the social impact of traditional culture. Despite the transition to a market economy, China's elite sports system remains centralised and government-controlled. The "Number 46" policy introduced in 2014 aimed to establish a world-leading sports industry by 2025. While the market has grown, promoting sport participation and addressing cultural influences and governmental control are essential for sustained future growth.